THE INFLUENCE OF WORK MORALE AND COMPENSATION ON EMPLOYEE PERFORMANCE AT PT. PANJI BINTANG JAYA WITH INDIVIDUAL CHARACTERISTICS AS INTERVENING VARIABLES - Ellen Nita Vindriana; Pompong B. Setiadi; Fanny Dwi Puspitasari (SEAN Institute, 2023)
The aim of this research is to test, prove and analyze the influence of work morale, compensation on employee performance with individual characteristics as intervening variables. This research uses primary data in the form of distributed questionnaire data. The sample used was 48 employees at PT. Panji Bintang Jaya, saturated sampling method. The analysis used in this research is SEM. Based on the research results, it can be concluded that the variables Work morale significantly influences individual characteristics, Compensation does not significantly influence individual characteristics, Work morale significantly influences employee performance, Compensation does not significantly influence employee performance, Work morale and compensation have a positive and significant influence on employee performance with individual characteristics as an intervening variable. The implications and suggestions are that it would be better if every employee complied with and adapted the culture that exists in the organization, such as compensation, work morale and individual characteristics. The information that has been obtained and analyzed can be made into studies such as the suitability of the objectives of compensation, work enthusiasm and individual characteristics that can be used to contribute to building the company. Compensation, work morale, individual characteristics and employee performance are very suitable to be used as the main study on the theme of HR development for Company employees.